2016
DOI: 10.1021/acsbiomaterials.6b00237
|View full text |Cite
|
Sign up to set email alerts
|

Direct Gradient Photolithography of Photodegradable Hydrogels with Patterned Stiffness Control with Submicrometer Resolution

Abstract: Cell response to matrix mechanics is well-known; however, the ability to spatially pattern matrix stiffness to a high degree of control has been difficult to attain. This study describes the use of maskless photolithography as a flexible process for direct, noncontact gradient patterning of photodegradable hydrogels with custom graphics. Any input gray scale image can be used to directly chart hydrogel cross-link density as a function of spatial position. Hydrogels can be patterned with submicron resolution, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
66
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(67 citation statements)
references
References 49 publications
1
66
0
Order By: Relevance
“…An efficient and versatile approach to overcome such limitations would be to develop a stiffness gradient platform that allows examination of the trend of the stiffness effect on the cell behavior at a glance with continuous stiffness change. Various techniques, including photochemical reactions with spatially controlled UV irradiation (Nemir, Hayenga, & West, ; Norris, Tseng, & Kasko, ; O'Connell et al, ; Sunyer, Jin, Nossal, & Sackett, ; Wong, Velasco, Rajagopalan, & Pham, ), physical crosslinking (Kim et al, ; Oh, An, Kim, & Lee, ), and diffusion‐based crosslinking (Hadden et al, ; Hartman, Isenberg, Chua, & Wong, ; Lee et al, ), have been suggested to realize the stiffness gradient platforms. The approaches were generally based on synthetic polymers or chemically modified natural polymers as substrate material, including polydimethylsiloxane (Wang, Tsai, & Voelcker, ), polyacrylamide (Hadden et al, ; Hopp et al, ; Sunyer et al, ), polyvinyl alcohol (Kim, An, et al, ; Oh et al, ), and gelatin (O'Connell et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…An efficient and versatile approach to overcome such limitations would be to develop a stiffness gradient platform that allows examination of the trend of the stiffness effect on the cell behavior at a glance with continuous stiffness change. Various techniques, including photochemical reactions with spatially controlled UV irradiation (Nemir, Hayenga, & West, ; Norris, Tseng, & Kasko, ; O'Connell et al, ; Sunyer, Jin, Nossal, & Sackett, ; Wong, Velasco, Rajagopalan, & Pham, ), physical crosslinking (Kim et al, ; Oh, An, Kim, & Lee, ), and diffusion‐based crosslinking (Hadden et al, ; Hartman, Isenberg, Chua, & Wong, ; Lee et al, ), have been suggested to realize the stiffness gradient platforms. The approaches were generally based on synthetic polymers or chemically modified natural polymers as substrate material, including polydimethylsiloxane (Wang, Tsai, & Voelcker, ), polyacrylamide (Hadden et al, ; Hopp et al, ; Sunyer et al, ), polyvinyl alcohol (Kim, An, et al, ; Oh et al, ), and gelatin (O'Connell et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…199 Surface gradients have also been generated using a maskless photolithography system that employed a digital micromirror device (DMD) to differentially expose regions of the hydrogel based on an input image (Figure 10b). 200 Here, any arbitrary image can be projected onto the hydrogel surface without the need to create a specific photomask. Using this technique, the authors were able to investigate the response of hMSCs to a pattern of repeating gradients, and that cells preferentially adhered to the most degraded regions.…”
Section: Photocleavage Reactionsmentioning
confidence: 99%
“…Scale bar 1 mm. Reprinted with permission from from Norris et al 200 copyright (2016) American Chemical Society.…”
Section: Figurementioning
confidence: 99%
“…Photolithography is one of the standard microfabrication techniques using a photoresist and a light source to fabricate hydrogel scaffolds for tissue engineering 67,68. When photoresists or light‐sensitive chemicals are exposed to light with or without optical mask, the patterns are transferred from optical mask to materials 69,70. In fabrication of hydrogels, photoresist‐containing biochemical cues are polymerized by exposure of light in the hydrogel.…”
Section: Photolithographymentioning
confidence: 99%
“…[67,68] When photoresists or light-sensitive chemicals are exposed to light with or without optical mask, the patterns are transferred from optical mask to materials. [69,70] In fabrication of hydrogels, photoresistcontaining biochemical cues are polymerized by exposure of light in the hydrogel. By using sliding optical mask or by Macromol.…”
Section: Photolithographymentioning
confidence: 99%